Iatrogenesis in Intensive Care Units: dramatization of Contemporary Bio/Ethical Problems (Revista Latino-Americana de Enfermagem, 2010)
This qualitative investigation, based in Foucauldian analysis with approximations to the post-structuralism theoretical framework, explores iatrogenesis as one of the tensions in the nursing to do/to know which can be discursively articulated to bioethics and to technobiomedicine. The documentary sources and intensive interviews with nurses, permitted the activation of a reflection on the act of the nurse in a context permeated by the ever-present possibility of failure in both the procedure and in the conduct and, from this possibility, they should meet their obligation to correct this failure not so much or not only in knowledge, not so much or not only in law but in practice itself.